The Facticity of Practices - Ginev, Dimitri (Journal of Psychology and Psychotherapy Research, 2018)
The paper sketches out the philosophical project for a hermeneutic theory of social practices. The theory gains its interpretive character by modeling the relations between the subjectivity involved in collective agency and the trans-subjectivity of concerted practices in terms of hermeneutic circularity. The main task of outlining such a theory is the overcoming of a dominant paradigm that consists in decomposing all assemblages of practices into manifolds of discrete elements determined by human agency. The strategy of overcoming this paradigm paves the way for working out a kind of conceptualizing the hermeneutic circularity which enables the autonomy of social practices. The paper argues that this conceptualization helps one to find a way out of the depressing dilemma between agency and structure.Actions and activities – as they are situated in and entangled with interrelated practices – neither causally determine nor impose norms on the ways in which practices are interrelated in their performances.An autonomous ensemble of social practices projects its being upon a horizon of possibilities which agents choose in accordance with their desires, plans, intentions, projects, moods, ambitions, presuppositions, prejudices, background and tacit knowledge. In the hermeneutic theory of practices, there is an important caesura that takes place in the passage from what human agency strongly determines to the authenticity manifested by the modes of being-in-concerted-social-practices.